A study of maternal morbidity and mortality DUE to Pre eclampsia and eclampsia - Vidya A. Thobbi; Afreen Anwar (Al Ameen Medical College, 2017)
Background: Pre eclampsia and eclampsia is one of the leading causes of maternal morbidity and mortality worldwide. Eclampsia though still remains an obstetric enigma, and is a major problem in developing countries. Although the incidence of pre eclampsia and eclampsia is on the decline, still it remains major contributor to poor maternal outcome. In India-gestational hypertension continues to be responsible for the largest proportion of cases contributing to maternal morbidity and mortality. Aims & objectives: The main objective of the study is to analyse the case of pre eclampsia and eclampsia complicating pregnancy, its maternal outcome, study the consequences of hypertensive disorders contributing pregnancy and its management. Methods: All patients beyond 20 wks of pregnancy with hypertensive disorders complicating pregnancy admitted in Al Ameen Medical College Hospital, Bijapur during the two year three months study period were enrolled in the study. Results: Total hypertensive cases accounted for 234 i.e; out of which mild pre eclampsia accounted for 144 casesi.e; 61.5%,severe pre eclampsia 64 cases i.e, 27.4%;eclampsia 26 cases 11.1%. Conclusion: Pre eclampsia and eclampsia is of the leading causes of maternal morbidity and mortality worldwide. The early use of antihypertensive drugs, optimum timing of delivery and strict fluid balance, anticonvulsants in case of eclampsia will help to achieve successful outcome.